Nutritional status and associated factors among children with congenital heart disease in selected governmental hospitals and cardiac center,Addis Ababa Ethiopia - Rediet Woldesenbet; Rajalakshmi Murugan; Feven Mulugeta; Tamirat Moges (BMC, 2021)
Abstract Background Children with congenital heart disease are at risk for poor growth and under-nutrition compared with healthy children. The aim of this study was to assess the nutritional status of children with congenital heart disease and associated factors in selected governmental hospitals and cardiac center Addis Ababa, Ethiopia. Method Institutional based cross sectional study among 373 children aged under15 years was conducted from February to March; 2021G.c. Data was collected using structured questionnaire and chart review. Z-scores based on WHO reference ranges were used. Anthropometric z-scores based on WHO 2007 reference ranges were generated for each child. Weight-for-age z-scores for children 0-10 years and height-for-age and BMI-for-age z-scores for all children. Binary logistic regression was used for associated factors. Result A total of 373 children were participated in this study. The prevalence of wasting and stunting was 144(38.6%) and 134(35.9%) respectively. The prevalence of underweight and malnutrition in children under 10 years was 143(43.1%). Most of the children were diagnosed with VSD (36.7%). Children age group of 13 months-5 years were associated with wasting and underweight [AOR = 0.434, 95%CI: (0.231, 0.816)] and [AOR = 0.360, 95%CI: (0.183, 0.711)] respectively. Children diagnosed with PAH were 1.885 times more likely to be underweight [AOR = 1.885, 95%CI: (1.094, 3.246)]. When the hemoglobin level increases by every unit per g/dl the chance to be wasting and underweight decreases by 13.1 and 18.6%[AOR = 0.869, 95%CI: (0.792, 0.955)] and [AOR = 0.869, 95%CI: (0.792, 0.955)] respectively. The level of SPO2 is associated with stunting and underweight [AOR = 0.970, 95%CI: (0.943, 0.998)] and [AOR = 0.970, 95%CI: (0.943, 0.998)] respectively. Conclusion The prevalence of malnutrition in children with CHD is pretty high. Decreased level of hemoglobin and SPO2 was found to be associated factors for malnutrition in this case. There need to be a new strategy about including different health professional while care giving.